Pengembangan Dakwah Melalui Gerakan Kebudayaan - Ashadi Cahyadi (Institut Agama Islam Negeri Bengkulu, 2018)
Development of Da'wah through the Cultural Movement is a model in broadcasting religious teachings that must be considered, through the formation of jama'ah as a social unit (Community). The fact shows that the Indonesian people have a broad cultural diversity and diversity. The most important way that must be done is that a missionary leader, both individually and in groups, must be a figure who is always creative, innovative and tries to have a cultural representative who is then proven in the missionary movement. Every missionary movement needs to formulate a missionary plan whose content of mission remains in accordance with Islamic teachings contained in the Qur'an and Al-Sunnah.